Rekonstruksi Falsafah Madrasah Sebagai Lembaga Pendidikan Islam Yang Unggul - Ridhokusumo; Abdullah zaid; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2024)
The madrasa, as an Islamic educational institution, plays a central role in the development of knowledge and Islamic understanding within the Muslim community. This article discusses the philosophy underlying the madrasa education system and its contributions to the formation of character and morals among Muslim generations. The study examines the fundamental values that form the operational basis of madrasas, such as tawhid (monotheism), ethics, and a love for knowledge, and how these values are reflected in the curriculum and teaching methods. Additionally, the role of madrasas in shaping a strong religious identity while balancing religious and general knowledge is explored. Using a descriptive-analytical method, this research reveals that madrasas not only function as centers of religious education but also as institutions that cultivate integrity grounded in Islamic values. This article aims to provide new insights into the contribution of madrasas as educational institutions that prioritize moral and spiritual dimensions, along with the challenges they face in the context of modernizing Islamic education.